Strengthening Friendship and Synergy: ASPETRI Malang Regency Halal Bihalal Activity as an Effort to Strengthen the Organization - Wibowo, Teguh Setiawan; Rahman, Alief Putriana; Utami, Ndari Sri (Westscience Press, 2025)
The Halal Bihalal event held by ASPETRI Malang Regency took place on April 15, 2024, in Mendit, Malang, with approximately 40 participants. The event aimed to strengthen interpersonal bonds among members and enhance organizational synergy following the celebration of Eid al-Fitr. Beyond a moment of reunion, the event served as a platform for consolidation and aligning visions in the development of traditional herbal medicine. A gesture of care for participants' well-being was reflected through the distribution of wedang rempah, a traditional herbal drink known for boosting immunity and warming the body. This activity illustrates that the Halal Bihalal tradition not only reinforces social relationships but also functions as a cultural and health-based organizational strengthening strategy.